Kulturella föreställningar om åldrande och femininitet - Liliequist, Marianne (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2011)
There are different discourses concerning women and ageing in the media and within the field of research about elderly people. In the public discourse eldelry women are often associated with depression, poverty and weak health. The popular culture, with its worshipping attitude towards the young, has a great influence on the cultural conceptions of female ageing. At the same time new images of elderly women as desirable and attractive are presented in popular media. These images can be understood as expressions for re-negotiation of what ageing means, but also as age-denying since it is the youthfullness among the elderly which is emphasised as something positive. Many researchers stress the importance of separating the public discourse on ageing, which is found in the media, from the women's own experiences of ageing. Interview studies with elderly women have shown that women's experiences of ageing can appear in a number of different ways depending on life context. This theme issue poses questions on ageing and femininity from a number of stand points by comparing the medial and public discourses with the women's own experiences of ageing.